Pyrosequencing reveals diverse fecal microbiota in Simmental calves during early development - Klein-Jöbstl, Daniela; Schornsteiner, Elisa; Mann, Evelyne; Wagner, Martin; Drillich, Marc; Schmitz-Esser, Stephan (Frontiers in Microbiology, 2014)
From birth to the time after weaning the gastrointestinal microbiota of calves must develop into a stable, autochthonous community accompanied by pivotal changes of anatomy and physiology of the gastrointestinal tract. The aim of this pilot study was to examine the fecal microbiota of six Simmental dairy calves to investigate time-dependent dynamics of the microbial community. Calves were followed up from birth until after weaning according to characteristic timepoints during physiological development of the gastrointestinal tract. Pyrosequencing of 16S rRNA gene amplicons from 35 samples yielded 253,528 reads clustering into 5,410 operational taxonomic units based on 0.03 16S rRNA distance. Operational taxonomic units were assigned to 296 genera and 17 phyla with Bacteroidetes, Firmicutes and Proteobacteria being most abundant. An age-dependent increasing diversity and species richness was observed. Highest similarities between fecal microbial communities were found around weaning compared with timepoints from birth to the middle of the milk feeding period. Principal coordinate analysis revealed a high variance particularly in samples taken at the middle of the milk feeding period (at the age of approximately 40 days) compared to earlier timepoints, confirming a unique individual development of the fecal microbiota of each calf. This study provides first deep insights into the composition of the fecal microbiota of Simmental dairy calves and might be a basis for future more detailed studies.